AKTIVITAS DAN SELEKTIVITAS KATALIS Ni/H5NZA TERHADAP HIDRORENGKAH METIL OLEAT MENJADI SENYAWA HIDROKARBON FRAKSI PENDEK - Ratno Budiyanto; Donatus Setyawan; Novita Andarini (Jurnal Kimia Riset, 2018)
It has conducted on the activity and selectivity of Ni/H5NZA catalyst toward the hydrocracking of oleat methyl catalytic becomes short fraction hydrocarbon compounds with the variation of Ni concentration such as 1%, 2% and 3% (% w/w) for oleat methyl catalytic hydrocracking becomes short fraction hydrocarbon compounds (C5-C11 hydrocarbon). The catalyst is prepared by wet impregnation method, then followed by calcinations at 500oC, oxidation at 400oC and reduction at 500oC, each of them are followed by a stream of nitrogen, oxygen and hydrogen with ± 5mL/second in stream velocity. The characterization of catalyst includes the determination of Si/Al ratio, Ni metal that were impregnated by using AAS instrument, and the acid determination by using gravimetric method. The hydrocracking process is done in flow-fixed bed reactor at 500oC; the catalyst are heated at first and followed by the reactants which are heated in pyrolysis reactor up to it change into vapor, then they are moved into the hydrocracking reactor. The liquid from hydrocracking process is collected and analyzed by using Gas of Chromatography (GC) and Gas of Chromatography-Mass spectrometer (GC-MS). The characterization results showed in general that Si/Al ratio decreases after being impregnated by Ni metal. The amount of Ni metal almost reach a half of early Ni concentration which is impregnated. On the other hands, the acid amount of catalyst after being impregnated by Ni metal rise higher than those before being impregnated by Ni metal. The research showed that the activity and selectivity of Ni-2%/H5NZA catalyst is better in hydrocracking hydrocarbon compounds which are shorter. The activity of Ni-2%/H5NZA catalyst reaches 91.3041%. Meanwhile the selectivity is more selective in creating the hydrocarbon compounds with C5-C11 chain and more lead to the formation of alkane and alkene. Keywords: methyloleate, catalyst, Ni/H5NZ,hydrocracking